PERANCANGAN BUKU BAHASA LAMPUNG DALAM UPAYA MENINGKATKAN PENGETAHUAN ANAK USIA 5 SAMPAI 7 TAHUN - Mataram, Sayid; Faizal, Daffa Ramadiansyah (ASKARA: Jurnal Seni dan Desain, 2024)
Lampung language is one of Lampung Province's cultural assets. Lampung language is the Lampung people's mother tongue. However, the Lampung language is gradually being abandoned and is rarely spoken, particularly among children and young people. This study will look at the design of Lampung language books with illustrations in order to pique the attention of youngsters aged 5 to 7 years old in learning the Lampung language. Children can thus contribute to the preservation of the Lampung language. This article will explain components of reading and writing book creators, namely color aspects, illustration aspects, layout aspects, and content aspects. Keywords: book, culture, illustration, child